2009
DOI: 10.1039/b908260c
|View full text |Cite
|
Sign up to set email alerts
|

The role of surfaces in catheter-associated infections

Abstract: In this critical review the biocidal efficacies of a variety of antimicrobial coatings currently in use for catheter surfaces are discussed to formulate the best strategy for decreasing the risk of catheter-associated infections. The development of new coatings containing antimicrobial chemicals and light-activated antimicrobial agents, and their applicability for use in catheters are summarised (132 references).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
174
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(178 citation statements)
references
References 126 publications
(270 reference statements)
2
174
1
1
Order By: Relevance
“…More effective antibacterial films are needed at present due to the increasing resistance of pathogenic bacteria to synthetic antibiotics when administered for long times [2]. Recently, Mills et al [3], Parkin et al [4][5][6][7], Foster et al [8], Dunlop et al [9] and Yates et al [10] have reported antibacterial films of Ag and Cu films on glass and thin polymer films by chemical vapor deposition (CVD) and in some cases sputtering techniques.…”
Section: Introductionmentioning
confidence: 99%
“…More effective antibacterial films are needed at present due to the increasing resistance of pathogenic bacteria to synthetic antibiotics when administered for long times [2]. Recently, Mills et al [3], Parkin et al [4][5][6][7], Foster et al [8], Dunlop et al [9] and Yates et al [10] have reported antibacterial films of Ag and Cu films on glass and thin polymer films by chemical vapor deposition (CVD) and in some cases sputtering techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Also nosocomial infections due to antibiotic resistant bacteria are becoming more frequent developing into a serious problem associated with high health care costs. Recently, Mills et al [6], Parkin et al [7][8][9][10], Foster et al [11], Dunlop et al [12] and Yates et al [13] have reported antibacterial Ag, Cu, and TiO 2 coatings on glass and polymer films depositing the metal/oxides by CVD and sputtering techniques. Our laboratory has reported the antibacterial properties and kinetics of Ag-and Cu-modified textiles deposited by DC-magnetron, pulsed DC-magnetron and high power impulse magnetron sputtering (HIPIMS).…”
Section: Introductionmentioning
confidence: 99%
“…To control the ion release, focus has shifted from bulk silver to nanoscale coatings and doped solids or hydrogels, with impregnated catheters and wound dressings already in clinical use [3,4,22,23]. With the use of silver nanoparticles (Ag NPs) for example, a higher surface area will increase the Ag + release.…”
Section: Introductionmentioning
confidence: 99%